Studies of material deposition during boronization using quartz crystal microbalance in EAST - Yuming Liu; Rong Yan; Lei Mu; Baoguo Wang; Qian Long; Zhaohui Wang; Yefan Zhu; Yuxian Wen; Zengjie Li; Shuyue Sun; Rui Ding; Junling Chen (Nuclear Materials and Energy, 2025)
Boronization is a widely employed technique for controlling fuel recycling and suppressing impurities. It is expected to be a routine wall conditioning method in the fully tungsten (W) wall configuration of the International Thermonuclear Experimental Reactor (ITER). To evaluate boron (B) performance under ITER-relevant metal wall conditions, ion cyclotron range of frequency (ICRF)-assisted boronizations were conducted in the Experimental Advanced Superconducting Tokamak (EAST) from 2023 to 2024. Quartz crystal microbalances (QMBs) installed at the mid-plane of ports C (C-QMB) and J (J-QMB), positioned well beyond the limiter, were utilized for in-situ and real-time measurements of material deposition rates during boronization using sublimation of carborane. Deposition rates ranged from 0.31 to 3.40 μg cm-2h−1 at C-QMB and 0.04 to 16.95 μg cm-2h−1 at J-QMB, exhibiting more spatially uniform profiles than lithium (Li) coatings. Deposition behavior was systematically studied and found to depend on the locations of the carborane sublimation oven and ICRF antenna, the temperatures of both the oven and substrate, and the substrate material. Higher deposition rates were associated with elevated plasma parameters in closer proximity to the ICRF antenna, denser gaseous carborane near the oven, and increased oven temperature. In contrast, deposition was reduced on high-Z substrate (W) and at elevated first wall temperature (70 °C). These findings provide further information for the optimization of boronization strategies in future fusion devices.